The Vatican, Great Britain, and Relations with Germany, 1938–1940 - Conway, John S. (The historical journal, 1973)
The Vatican in the twentieth century has played a far less considerable role on the world's stage than in previous centuries. Stripped of its temporal possessions, the Vatican no longer exercises that military and political power which Napoleon estimated to be worth an army corps of 20,000 men, but which his latter day successor, Stalin, could sardonically dismiss with the (apocryphal) question: ‘How many divisions has the Pope?’ Nevertheless, the papacy remains an influential factor in world affairs; and there is still strong appeal in die ideal of the papacy pursuing aims which, in contrast to those of other powers, are solely peace and reconciliation.